An experimentally constrained MHD model for a collisional, rotating plasma column. (9th December 2016) - Wright, A M; Qu, Z S; Caneses, J F; Hole, M J
Abstract: A steady-state single fluid MHD model which describes the equilibrium of plasma parameters in a collisional, rotating plasma column with temperature gradients and a non-uniform externally applied magnetic field is developed. Two novel methods of simplifying the governing equations are introduced. Specifically, a 'radial transport constraint' and an ordering argument are applied. The reduced system is subsequently solved to yield the equilibrium of macroscopic plasma parameters in the bulk region of the plasma. The model is benchmarked by comparing these solutions to experimental measurements of axial velocity and density for a hydrogen plasma in the converging-field experiment MAGPIE and overall a good agreement is observed. The plasma equilibrium is determined by the interaction of a density gradient, due to a temperature gradient, with an electric field. The magnetic field and temperature gradient are identified as key parameters in determining the flow profile, which may be important considerations in other applications.